Glimpses of world histoy - Nehru, Jawaharlal (Gurugram Penguin, 2004)
Glimpses of the World History' is an account of the progress of the world through centuries and ages. This book is a collection of letters that Jawaharlal Nehru wrote to his daughter Indira when he was in various Indian prisons for three years. The letters were meant to introduce her to the world and its history. In the first few letters, Nehru expresses his sadness for not being able to be around his daughter and give her the materialistic gifts that other parents could but he promises to give her a gift that he could afford; in the form of knowledge and wisdom through words that come from the very core of his heart. Nehru wrote 196 letters and covered the history of mankind from 6000 BC to the time he was writing the letters.
Keywords: Indian Freedom Struggle- Nehru, Jawaharlal